2016
DOI: 10.1111/jfs.12272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance of Salmonella SPP. and Salmonella Typhimurium in Broiler Carcasses Wings and Liver

Abstract: The objectives of this study were to isolate and identify Salmonella spp. from broiler carcasses, wings and liver samples by immunomagnetic separation based cultivation technique, to verify the isolates as Salmonella spp. by the detection of oriC gene by PCR, to identify the isolates using malic acid dehydrogenase and DT104 specific primers as S. Typhimurium and S. Typhimurium DT104. Also to determine the two important virulence genes, virulence plasmid (spvC) and invasion (invA) for molecular characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…According to our study, all the isolates were determined as resistant or intermediate to at least one antibiotic used in study and which is a significant public health concern. Goncuoglu et al (11) also implied that ongoing surveillance and antibiotic resistance of foodborne pathogens in the food chain is essential due to the public health implementations. Besides, by the reason of high antibiotic resistance profiles, it is very crucial to analyze antibiotic profiles of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, all the isolates were determined as resistant or intermediate to at least one antibiotic used in study and which is a significant public health concern. Goncuoglu et al (11) also implied that ongoing surveillance and antibiotic resistance of foodborne pathogens in the food chain is essential due to the public health implementations. Besides, by the reason of high antibiotic resistance profiles, it is very crucial to analyze antibiotic profiles of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…As per (Wang, 2016), the difference between Salmonella prevalence in our study and others reported in the literature could be due to difference in the study design particularly number of samples collected, sample collection period, sample type, sampling procedures and method of detection used. Studies conducted in China, Greece and the USA described that prevalence and concentration of Salmonella in chicken was relatively higher in summer and spring than winter and autumn (Rodriguez et al (Goncuoglu, Ormanci, Uludag, & Cil, 2016). The emergence of high resistance of Salmonella to tetracycline, amoxicillin and trimethoprim antimicrobials in the study may be contributed to indiscriminate use of these antimicrobials in poultry production as growth promotion, prophylactic and therapeutic purposes (Nourouzi, Mirzaii, & Norouzi, 2004) and Bhutan is no exception.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, among the serotypes most frequently seen in humans all over the world, S. Typhimurium was not detected and S. Enteritidis was the 5th most common isolated serotype in this study. There is limited data relating with laying hen Salmonella contamination in Turkey but according to the previous studies S. Typhimurium contamination was rare in poultry meat and products [28,29]. In another study performed in Turkey, overall Salmonella infection rate was 18.2% in 14 chicken layer breeder flocks analysed by PCR and conventional culture methods [30].…”
Section: Resultsmentioning
confidence: 99%